2014
DOI: 10.1242/jeb.097402
|View full text |Cite
|
Sign up to set email alerts
|

The role of the olfactory recess in olfactory airflow

Abstract: The olfactory recess -a blind pocket at the back of the nasal airway -is thought to play an important role in mammalian olfaction by sequestering air outside of the main airstream, thus giving odorants time to re-circulate. Several studies have shown that species with large olfactory recesses tend to have a well-developed sense of smell. However, no study has investigated how the size of the olfactory recess relates to air circulation near the olfactory epithelium. Here we used a computer model of the nasal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…We performed a grid-refinement study by examining patterns and rates of flow in models with twice and four times as many bricks. We did not find notable differences in either parameter, corroborating our previous work [4], and indicating that the approximately 625 000-tetrahedra models were sufficient for this study.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…We performed a grid-refinement study by examining patterns and rates of flow in models with twice and four times as many bricks. We did not find notable differences in either parameter, corroborating our previous work [4], and indicating that the approximately 625 000-tetrahedra models were sufficient for this study.…”
Section: Methodssupporting
confidence: 91%
“…The implication of this finding is that, rather than sequestering recently inhaled air from exhalation, the primary functions of the olfactory recess in these phyllostomid bats may be to expand the surface area available for the olfactory epithelium and slow down inhaled air to improve odorant absorption across this epithelium. Some computational support for this idea was found by Eiting et al [4], who showed in an experimental modelling study that, all else being equal, a larger olfactory recess produces lower rates of flow through this region during exhalation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations